2008
DOI: 10.1080/00015458.2008.11680302
|View full text |Cite
|
Sign up to set email alerts
|

Benign Intracranial Hypertension with Recurrent Spontaneous Cerebrospinal Fluid Rhinorrhoea Treated by Laparoscopic Gastric Banding

Abstract: We present the case of a 45-year-old woman presenting with a spontaneous cerebrospinal fluid (CSF) rhinorrhoea. A CSF leak, arising from a posterior ethmoidal left cell, was closed using an underlay procedure with a turbinate composite graft with applied fibrin glue. Twenty-three months later the CSF rhinorrhoea recurred. Recurrence was imputed to morbid obesity (BMI 48) responsible for benign intracranial hypertension. The patient underwent a laparoscopic adjustable gastric banding. CSF rhinorrhoea gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In previously reported cohorts of patients with spontaneous CSF leaks, CSF pressures preoperatively have been well above the normal range . There are many reported methods of ICP management in the literature including the standard treatments of acetazolamide or permanent CSF diversion as well as diet, serial lumbar punctures, and bariatric surgery . The management of elevated ICP in patients being treated for spontaneous CSF rhinorrhea in our prospective case series was accomplished either with acetazolamide, a diuretic that decreases CSF production, or permanent CSF diversion via ventriculoperitoneal shunt.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In previously reported cohorts of patients with spontaneous CSF leaks, CSF pressures preoperatively have been well above the normal range . There are many reported methods of ICP management in the literature including the standard treatments of acetazolamide or permanent CSF diversion as well as diet, serial lumbar punctures, and bariatric surgery . The management of elevated ICP in patients being treated for spontaneous CSF rhinorrhea in our prospective case series was accomplished either with acetazolamide, a diuretic that decreases CSF production, or permanent CSF diversion via ventriculoperitoneal shunt.…”
Section: Discussionmentioning
confidence: 74%
“…14 There are many reported methods of ICP management in the literature including the standard treatments of acetazolamide or permanent CSF diversion as well as diet, serial lumbar punctures, and bariatric surgery. 8,10,26,27 The management of elevated ICP in patients being treated for spontaneous CSF rhinorrhea in Al-Sebeih et al 69 42.9 (25- our prospective case series was accomplished either with acetazolamide, a diuretic that decreases CSF production, or permanent CSF diversion via ventriculoperitoneal shunt. Some authors reported temporary use of lumbar drains in the postoperative period, but did not measure ICPs or utilize methods for long-term control of elevated ICP.…”
Section: Discussionmentioning
confidence: 99%
“…Diet and gastric surgery have proven useful in reducing intracranial pressure and its consequences. [29][30][31] It should be noted that non-obese patients may also suffer from intracranial hypertension, which may go unnoticed if not specifically investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, other factors associated with failure of the CSF leak repair include obesity (common in IIH) and difficult visualization of the site of leak (e.g. lateral sphenoid leaks) (21). Since increased ICP is the main cause of failure, appropriate ICP-lowering management is suggested to improve the success rates of a definite repair of the CSF leak.…”
Section: Discussionmentioning
confidence: 99%